2003
DOI: 10.1016/s0009-9236(03)00238-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple transport mechanisms involved in the intestinal absorption and first-pass extraction of fexofenadine,

Abstract: In this in vivo perfusion study verapamil increased the bioavailability of fexofenadine. Because the permeability, which is a direct measure of intestinal transport, was unchanged, we suggest that the major reason for this effect was decreased first-pass liver extraction of fexofenadine. The most plausible mechanism is either decreased organic anion transporting polypeptide-mediated sinusoidal uptake or P-glycoprotein-mediated canalicular secretion of fexofenadine, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
80
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 43 publications
9
80
3
Order By: Relevance
“…The E H is dependent on the blood flow (Qh), protein binding (fu) and intrinsic clearance of the enzymes or transporters (Clint) (Rowland & Tozer 1995). Recently, it has also been recognized that membrane transport into the hepatocyte has to be included in the models for predicting and explaining liver extraction (Tannergren et al 2003a;Chandra & Brouwer 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The E H is dependent on the blood flow (Qh), protein binding (fu) and intrinsic clearance of the enzymes or transporters (Clint) (Rowland & Tozer 1995). Recently, it has also been recognized that membrane transport into the hepatocyte has to be included in the models for predicting and explaining liver extraction (Tannergren et al 2003a;Chandra & Brouwer 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted by our group showed reduction of the p.o. area under the blood-concentration time curve (AUC) for fexofenadine [P-gp, OATP substrate (Cvetkovic et al, 1999;Tannergren et al, 2003;Shimizu et al, 2005;Kikuchi et al, 2006;Bailey et al, 2007)] in the presence of GF120918 (P-gp inhibitor) in the rat with concomitant dosing of RIF [OATP inhibitor (Vavricka et al, 2002;Garver et al, 2006)], so RIF was selected as a model Oatp inhibitor in the present studies. Additional in vivo studies were conducted to explore whether RIF administration reduced macrolide p.o.…”
mentioning
confidence: 99%
“…Earlier in vitro results have shown that fexofenadine is transported by various mechanisms across biological membranes, including transcellular passive diffusion and, to some extent, P-glycoprotein (ABCB1) and organic anion-transporting polypeptides (OATPs) (Cvetkovic et al, 1999;Dresser et al, 2002;Perloff et al, 2002;Kobayashi et al, 2003;Nozawa et al, 2004;Petri et al, 2004). Several clinical studies have reported drug-drug and drug-diet interactions between fexofenadine and substrates or inhibi-tors of both these transporters (Davit et al, 1999;Hamman et al, 2001;Dresser et al, 2002;Wang et al, 2002;Tannergren et al, 2003b).…”
mentioning
confidence: 99%
“…However, the study conducted with verapamil demonstrated that the systemic exposure of fexofenadine increased 4-fold in the presence of the inhibitor (Tannergren et al, 2003b). It was suggested that this result could be related to inhibition of verapamil on the OATP-mediated liver uptake from the sinusoids and/or secretion of canalicular ABCB1 into the bile (Cvetkovic et al, 1999;Perloff et al, 2002;Petri et al, 2004).…”
mentioning
confidence: 99%